Does the indicator of relative need (IoRN2) tool improve inter-professional conversations?. Issue 4 (8th September 2021) - Barron, Wendy; Gifford, Elaine; Knight, Peter; Rainey, Helen
Abstract : Purpose: This paper provides an overview of an improvement project that explored whether the implementation of IoRN2, a validated freely available tool designed for any health or social care professional to use, resulted in improved conversations across professions within an integrated rehabilitative reablement service. Design/methodology/approach: A qualitative descriptive evaluative approach was applied underpinned by quality improvement Lean and Total Quality Management (TQM) to capture perceptions, variables and IoRN2 value-add. Professionals' ( N  = 8) across Nursing, Allied Health Professions, Social Work, Quality Improvement and Support Workers participated in one-to-one semi-structured <1 h interviews. Recurring themes and experiences were identified. Findings: IoRN2 improved collaborative conversations. The evaluation of the tool demonstrated greatest impact when all professionals were IoRN2 trained. Participants, regardless of profession, believed that their conversations, professional relationships and outcomes improved when using IoRN2. When differing judgments arose with colleagues who were not IoRN2 trained, fear and tension emerged around trust, cultural manners and power play causing disconnects. Incorporating IoRN2 led to psychologically safe environments where trust, confidence and motivation to explore new creative conversations enhanced strength-based outcomes and helped to generate transformational change. Research limitations/implications: The small sample size offered transferable learning worthy of larger future study. The project lead was also the reablement service manager, which may have generated unintended influence. Originality/value: IoRN2 has the potential to improve how HSC professionals converse, acting as a catalytic tool for system-level integration, transformation and sustainable improvement.